The Movement of slow: From English to Italian and Back Again. A Diachronic Corpus-Based Study - Nocella, Jessica Jane; Bondi, Marina (Elephant & Castle, 2024)
The present study explores the changes in the meaning of the word slow, both in Italian and English, from the beginning of the Slow Food Movement (SFM) up to 2019. Since 1989 and the early days of Carlo Petrini’s SFM, technology has increasingly led people towards multi-tasking in an attempt to save time, while at the same time, back to the past trends are increasingly evident as seen in several other Slow Movements, for example, in catering and hand-made/retro chains. The concept of slowness is becoming a relevant and ethical topic that is often related to what is organic, local and sustainable, leading to the introduction of an anglicism in Italian, but also to a new whole re-semantization of the word slow in English. The primary objective of this study is to explore the semantic changes in the word slow diachronically both in Italian and in English. To this aim, two robust corpora were created, one from the Italian newspaper La Stampa and the other from the British The Guardian. The word slow was analysed within the different newspaper domains exploring frequencies, collocates, and identifying significant “repeated events” (Sinclair 2004: 28) together with their semantic preferences. Results from the diachronic analysis show that through the SFM, the word slow has taken on specific new meanings in Italian, related to the dimensions of ethics, wellbeing, and environmental awareness. These were then partly re-introduced in English. More specifically, the case of reborrowing of slow within the context of movements (slow fashion, slow tourism, etc.) has quite likely been influenced by the Italian SFM. As a matter of fact, this process of reborrowing involves both acquisition and loss in meaning in both languages. This seems to be a relevant phenomenon in a global context of constant linguistic contact where English appears to play a relevant role as a global language.